Progressivity of Legal Protection in Realizing Social Justice for Domestic Workers - Jurdi, Fajlurrahman; Mitmainnah, Nurul; Syafiin, Rezky Amalia (Faculty of Law, Khairun University, 2017)
Legal protection of domestic workers in Indonesia currently does not have a legal regulation. The Manpower Law also does not accommodate legal protection for domestic workers who are not considered as a worker. The only one regulation related to domestic workers in Indonesia is a ministerial regulation with a legal force that does not accommodate all the fulfillment of rights and obligations that are unclear to domestic workers especially who are recruited directly. The government has not yet established a special agency/ institution to provide legal protection for domestic workers that make Non-Government Organization (NGO) involved more in handling this matter. The absence of a legal regulation for the protection of domestic workers is a major cause of rights violations for domestic workers itself. In dealing with these conditions, the authors propose the need for the establishment of special law of domestic workers who are recruited directly and manifested through the establishment of the Domestic Workers Handling Institution as a solutive step in realizing civilized justice for domestic workers as a worker.Ã‚Â The formation can be done in several ways, first, providing legal certainty and guarantee through the establishment of a specially hired domestic labor law, which includes the rights, and obligations of workers and employers. Secondly, to establish an institute for Domestic Workers Handlings that have the competence such as data of domestic worker, training and protection for domestic worker as a worker. In this writing, the author uses primary, secondary, and non-legal material. Legal material is obtained through literature research method then the material obtained is analyzed qualitatively and presented descriptively. The expected outcome is the realization of legal protection for domestic workers as a worker who is recruited directly as mandated by the constitution.